Artificial Intelligence and Imaging for Diagnostic and Treatment Challenges in Breast Care: First Deep Breast Workshop, Deep-Breath 2024, Held in Conjunction with MICCAI 2024, Marrakesh, Morocco, October 10, 2024, proceedings - Mann, Ritse M.; Zhang, Tianyu; Tan, Tao; Han, Luyi; Truhn, Daniel; Li, Shuo; Gao, Yuan; Doyle, Shannon; Martí Marly, Robert; Kather, Jakob Nikolas; Pinker-Domenig, Katja; Wu, Shandong; et al. (Lecture Notes in Computer Science, 2025)
This book constitutes the refereed proceedings of the First Deep Breast Workshop on Artificial Intelligence and Imaging for Diagnostic and Treatment Challenges in Breast Care, Deep-Breath 2024, held in conjunction with the 26th International Conference on Medical Imaging and Computer-Assisted Intervention, MICCAI 2024, in Marrakesh, Morocco, on October 10, 2024.The 23 regular papers presented in this book were carefully reviewed and selected from 51 submissions.The workshop provides an international platform for presentation of - and discussion on - studies related to AI in breast imaging. Deep-Breath aims to promote the development of this research area by sharing insights in academic research and clinical practice between clinicians and AI experts, and by exploring together the opportunities and potential challenges of AI applications in breast health. The deep-breath workshop provides, therefore, an unique forum to discuss the possibilities in this challenging field, aiming to create value that eventually truly leads to benefit for physicians and patients